High nickel positive electrode material for lithium ion batteries, manufacturing method and use

By adding modified elements to the high-nickel positive electrode material and performing multiple calcination and coating treatments, a material with porous and crystal structure is formed, which solves the problem that the prior art is difficult to achieve high-rate characteristics, high capacity, long cycle life and low DC internal resistance at the same time, and achieves efficient cobalt free positive electrode material performance.

JP7662608B2Active Publication Date: 2025-04-15GUIZHOU ZHENHUA E CHEM INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022211110
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-31
Filing Date
2022-12-28
Publication Date
2025-04-15
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

The prior art is difficult to achieve cobalt free cathode materials with high rate characteristics, high capacity, long cycle life and low DC internal resistance at the same time.

Method used

Using a high nickel positive electrode material, a material with a unique porous structure and crystal structure is formed by adding modification elements and performing at least two calcination and coating treatments.

Benefits of technology

The high capacity, good rate characteristics and excellent structural stability of the high nickel positive electrode material are achieved, reducing capacity loss and internal resistance increase during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662608000006
    Figure 0007662608000006
  • Figure 0007662608000007
    Figure 0007662608000007
  • Figure 0007662608000001
    Figure 0007662608000001
Patent Text Reader

Abstract

To provide a high-nickel positive electrode material for a lithium-ion battery, which has good cycle characteristics, high capacity, and a relatively small increase in impedance during cycling of the battery, a manufacturing method and a usage thereof.SOLUTION: A high nickel cathode material for a lithium ion battery has a porous structure and an elemental composition represented by the chemical formula Li1+aNibMncAdO2, 0.01≤a≤0.24, 0.79<b≤0.96, 0.01<c≤0.20, 0<d≤0.06 are satisfied, A is selected from one or more elements selected from Mn, Co, Al, Zr, Y, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, Ca, V, Sc, Sr, and B, or selected from phosphorus-containing compounds containing at least one element selected from Ti, Al, Mg, Zr, La, and Li.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of lithium ion batteries, and relates to high nickel positive electrode materials for lithium ion batteries, and their manufacturing methods and applications. [Background technology]

[0002] In 2019, the new energy market has undergone dramatic changes, and the number of electric vehicles continues to increase, which has led to an ever-increasing need for the energy density and cost-effectiveness of lithium-ion batteries. Among them, in the lithium-cobalt-nickel-manganese ternary cathode material, cobalt is a scarce resource and expensive, so in order to improve cost-effectiveness and ensure high energy density, the amount of cobalt used can be reduced by appropriately increasing the content of nickel or manganese elements. Increasing the nickel content can provide a high-capacity battery, but the increased nickel content makes the material structure unstable and prone to react with the electrolyte solution, and repeated charging and discharging can cause cracks in the cathode material, shortening the cycle life of the lithium-ion battery, increasing the impedance, and reducing the capacity. Therefore, it is urgent to develop or find new materials to replace the scarce resource cobalt or reduce the amount of cobalt used in the material.

[0003] Chinese Patent CN102280636A discloses a positive electrode active material, its manufacturing method and a lithium secondary battery containing the same, the positive electrode active material of the lithium secondary battery being obtained by preparing a precursor by coprecipitation, then mixing with a lithium source and carrying out a calcination treatment, the material contains pores with an average diameter of about 10 nm to about 60 nm, and the porosity of the material is about 0.5% to about 20%, the material has good particle strength, so that crushing after pressing is prevented or reduced, the material is not easily reactive with the electrolyte and exhibits good thermal stability, so that a high capacity lithium secondary battery can be provided. However, the chemical formula of the material is Li a Ni x Co y Mn z M kAs can be seen from O2 (where 0.45 ≦ x ≦ 0.65, 0.15 ≦ y ≦ 0.25, 0.15 < z ≦ 0.35), the cobalt content of the material is high and the capacity is insufficient, so the cost-effectiveness cannot meet the requirements.

[0004] Chinese Patent CN108123119A discloses a nickel-based active material for a lithium secondary battery, a method for manufacturing the same, and a lithium secondary battery including a positive electrode including the same. In this patent, a mixture of a lithium precursor and a metal hydroxide is heat-treated at a low temperature in an oxygen atmosphere and then heat-treated at a high temperature to obtain a nickel-based active material. The material includes secondary particles including aggregates of two or more plate-shaped primary particles, and at least a part of the secondary particles includes a structure in which the plate-shaped primary particles are radially arranged. The outside of the secondary particles has a higher porosity (pore rate) than the inside of the secondary particles. However, this patent does not mention which field of problems is improved.

[0005] Chinese Patent CN1856890 discloses lithium composite oxide particles for a lithium secondary battery positive electrode, a lithium secondary battery positive electrode using the particles, and a lithium secondary battery. This patent discloses lithium composite oxide particles for a lithium secondary battery electrode material and explains that it can improve the low-temperature load characteristics of the battery and the coating property during positive electrode manufacturing. The material must satisfy the following condition (A) in the measurement using the mercury intrusion method and at the same time satisfy at least one of the following conditions (B) and condition (C). Condition (A): In the mercury intrusion curve, when the pressure increases from 50 MPa to 150 MPa, the mercury intrusion amount is 0.02 cm 3 / g or less. Condition (B): In the mercury intrusion curve, when the pressure increases from 50 MPa to 150 MPa, the mercury intrusion amount is 0.01 cm 3 / g or more. Condition (C): The average pore radius is 10 - 100 nm, and the pore size distribution curve has a main peak with the upper end located at a pore radius of 0.5 - 50 μm and a sub-peak with the upper end located at a pore radius of 80 - 300 nm. This patent mainly focuses on low-temperature characteristics and does not consider high-temperature characteristics.

[0006] Chinese Patent CN104272520A discloses a non-aqueous electrolyte secondary battery and a manufacturing method thereof. In the patent, the positive electrode composite layer constituting the positive electrode of the non-aqueous electrolyte secondary battery has a differential pore volume peak A in a pore diameter range of 0.05 μm to 2 μm and a peak B located on the smaller pore diameter side than the peak A in a pore distribution curve measured by a mercury porosimeter, and the pore distribution curve has a minimum point C between the peak A and the peak B where the differential pore volume is a minimum value, and the differential pore volume X of the peak A is A and the differential pore volume X of the peak B B The larger differential pore volume of L The differential pore volume X of the minimum point C C Ratio to (X C / X L ) is 0.6 or more. The patent mainly reduces problems such as gassing of batteries by adding an overcharge additive during the battery manufacturing process.

[0007] Chinese patent CN112993239A discloses a high-pressure, low-cobalt ternary positive electrode material and its manufacturing method. The positive electrode material is made from a precursor containing nickel, cobalt and manganese, a lithium source, and an additive containing a metal element, and is mainly composed of (Ni 0.5 Co 0.1 Mn 0.4 The cathode material is obtained at low, medium and high temperatures using 1,2-dichloro-1,3 ...

[0008] Chinese patent CN108963218A discloses a method for preparing and using a low-cobalt, high-nickel ternary lithium cathode material, which is prepared by mixing nickel nitrate, titanium nitrate and manganese nitrate in a molar ratio of 8.75:0.25:1 to obtain an aqueous solution, which is then spray-dried to obtain a precursor, and then using an inducer to induce the exchange of titanium and cobalt. The precursor, inducer and lithium hydroxide are used to prepare a suspension in a predetermined molar ratio, which is spray-dried and then calcined to obtain the cathode material. The material has a much lower cobalt content while greatly improving thermal stability, cycle life and safety. However, the material is mainly obtained by only one calcination to obtain the finished product, and due to the limited calcination time, sufficient time and kinetic energy cannot be provided, and the structure of the material cannot be well synthesized, which does not necessarily result in cycle performance and thermal stability.

[0009] Chinese patent CN112811475A discloses a monocrystalline cathode material, its manufacturing method and a lithium ion battery, which explains that the monocrystalline precursor is obtained by air-milling large particles of a polycrystalline precursor, and lithium is added and sintered to obtain the cathode material. This method has a simple process and reduces the manufacturing cost compared to the wet method. The material is finished by only one sintering, and the sintering time is limited, so the time and kinetic energy cannot be provided, and the structure of the material cannot be well synthesized, and the cycle property and thermal stability property cannot be obtained.

[0010] Chinese Patent CN112750999A discloses a positive electrode material and its manufacturing method, and a lithium-ion battery, the positive electrode material comprising a high nickel-free cobalt-free multi-component positive electrode material intermediate and a cobalt-containing compound coating the outer surface of the high nickel-free cobalt-free multi-component positive electrode material intermediate, and the content of cobalt element in the cobalt compound is 0.5-5 mol% of the total moles of nickel and manganese. The material produced by this method has a stable structure, high energy density, excellent rate characteristics, and high capacity retention. However, the free lithium of the material is high, and gel is generated during the pulp production process, which may affect the processing of the battery. Summary of the Invention [Problem to be solved by the invention]

[0011] The reduction of the cobalt content reduces the structural stability of the cobalt-free material and the ternary material, and the capacity, rate characteristic, and cycle characteristic of the material cannot be normally exhibited. Therefore, various methods have been proposed according to different specification requirements. When high cycle characteristics and safety are required, high temperature sintering is used to obtain large single crystal materials. When high rate characteristics are required, low temperature sintering is used to obtain secondary particles with very small primary particles, but such methods have defects in the actual use of the battery.

[0012] The technical problem to be solved by the present invention is that the cobalt-free positive electrode material of the prior art cannot simultaneously realize high rate characteristics, high capacity, long cycle life, and low DC internal resistance. The present invention provides a high nickel positive electrode material for lithium ion batteries and a manufacturing method thereof, which is obtained by adding a modifying element and performing at least two firings and one coating process. The positive electrode material has a porous structure, which provides more paths for the movement of lithium ions and a shorter path, so that the lithium ion battery not only has a higher capacity but also has good rate characteristics. The lithium ion battery also has good structural stability, and during the charging and discharging of the lithium ion battery, the capacity loss is small, the cycle characteristics are excellent, and the increase in DC internal resistance is small. The present invention further provides a positive electrode and a lithium ion battery comprising the positive electrode material for lithium ion batteries, and further provides the use of the high nickel positive electrode material for lithium ion batteries or the positive electrode of lithium ion batteries or the lithium ion battery in the field of digital batteries, power batteries, or storage batteries. [Means for solving the problem]

[0013] The technical solutions of the present invention are as follows: The present invention provides a high-nickel positive electrode material for a lithium-ion battery, the high-nickel positive electrode material having a porous structure, The chemical formula 1 is Li 1+a Ni b Mn c A d O2, where 0.01 ≦ a ≦ 0.24, 0.79 < b ≦ 0.96, 0.01 < c ≦ 0.20, 0 < d ≦ 0.06, and A is selected from any one or more elements of Mn, Co, Al, Zr, Y, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, Ca, V, Sc, Sr, and B, or is selected from a phosphorus-containing compound containing at least one element of Ti, Al, Mg, Zr, La, and Li.

[0014] Preferably, when measured by the nitrogen adsorption method, in the BJH pore size distribution curve, it has a single-peak or multi-peak pore size distribution within the range of pore sizes of 1.5 to 20 nm, and the high-nickel cathode material has a total pore volume of 0.0 1c m 3 / g or less, preferably 0.00 7c m 3 / g or less.

[0015] Preferably, in the powder X-ray diffraction pattern of the cathode material, the full width at half maximum FWHM(101) of the diffraction peak at a diffraction angle 2θ of around 36.6° in the powder X-ray diffraction pattern of the cathode material is 0.080 to 0.180.

[0016] Preferably, the Dv50 particle size of the cathode material is 3 to 20 μm.

[0017] Preferably, the specific surface area of the cathode material is 0.33 to 1.5 m 2 / g, and / or the tap density of the cathode material is 1.9 g / cm 3 or more, and / or the total free lithium amount of the cathode material is less than 1800 ppm.

[0018] Preferably, in the chemical formula 1, 0.001 ≦ d ≦ 0.04.

[0019] The present invention further provides a method for preparing said high nickel positive electrode material for lithium ion batteries, comprising mixing the raw materials followed by at least two firing steps and one coating step.

[0020] Preferably, the first firing temperature is 700 to 900° C., preferably 790 to 890° C., and more preferably, the constant temperature time is 8 to 40 hours. and / or the second firing temperature is 400 to 800°C, preferably 680 to 800°C, and more preferably the constant temperature time is 5 to 20 hours; More preferably, the firing atmosphere is oxygen.

[0021] Preferably, the coating process is carried out before the final firing.

[0022] Preferably, in the production method, the Li source is a lithium-containing oxide, a lithium-containing fluoride, or a lithium-containing salt, and preferably, the Li source is one or more selected from anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium acetate, and lithium fluoride.

[0023] Preferably, the precursor in the raw material has a Dv50 particle size of 2.0 to 20 μm.

[0024] The present invention further provides a high nickel positive electrode material for lithium ion batteries produced by the above-mentioned method.

[0025] The present invention further provides a high nickel cathode material for lithium ion batteries comprising two or more of the above cathode materials.

[0026] The present invention further provides a lithium ion battery cathode comprising a current collector and a cathode material supported on the current collector, said cathode material being a high nickel cathode material for said lithium ion battery.

[0027] The present invention further provides a lithium ion battery comprising a positive electrode, a negative electrode, and a lithium salt-containing electrolyte, the positive electrode being the lithium ion battery positive electrode.

[0028] The present invention further provides the use of said high nickel positive electrode material for lithium ion batteries, or said lithium ion battery positive electrode, or said lithium ion battery in the field of digital batteries, power batteries or accumulator batteries. Effect of the Invention

[0029] The beneficial effects of the present invention are as follows: Compared with ordinary lithium ion battery positive electrode materials, the present invention obtains a cobalt-free modified high nickel lithium ion battery positive electrode material by adding a modifying element and performing at least two sintering processes and one coating process, which has a unique porous structure and crystal structure, and the porous structure of the positive electrode material provides more paths for the movement of lithium ions and the paths are shorter, so that the lithium ion battery not only has higher capacity and good rate characteristics, but also has excellent structural stability due to the crystal structure, and during the charging and discharging of the lithium ion battery, the capacity loss is small, the cycle characteristics are excellent, and the increase in DC internal resistance is small, so that the capacity, rate characteristics and cycle characteristics of the cobalt-free positive electrode material are effectively balanced. [Brief description of the drawings]

[0030] [Figure 1] FIG. 1 is the pore size distribution curve of the high nickel positive electrode material produced in Example 7. [Diagram 2] FIG. 2 is an X-ray diffraction pattern of the high nickel positive electrode material produced in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] To clearly and completely describe the technical solution according to the embodiments of the present invention so that the purpose, technical solution, and technical effect of the embodiments of the present invention become clearer, the following described embodiments are not all embodiments of the present invention but are part of the embodiments of the present invention. If those skilled in the art obtain other embodiments from the embodiments of the present invention without performing novel operations, all of them belong to the protection scope of the present invention.

[0032] In the description of the present invention, the term "multi-peak" refers to a pore size distribution in which the BJH pore size distribution curve includes two or more maximum values of pore volume. Generally, the maximum value of pore volume is 0.000 8c m 3 / g or more.

[0033] In the description of the present invention, the term "single-peak" refers to a pore size distribution in which the BJH pore size distribution curve includes one maximum value of pore volume. Generally, the maximum value of pore volume is 0.000 8c m 3 / gmata is or more.

[0034] Hereinafter, to better understand the above technical solution, the present invention will be described in more detail.

[0035] The present invention provides a high-nickel cathode material for lithium-ion batteries. The high-nickel cathode material has a porous structure, and its chemical formula 1 is Li 1+a Ni b Mn c A d O2, where 0.01 ≤ a ≤ 0.24, 0.79 < b ≤ 0.96, 0.01 < c ≤ 0.20, 0 < d ≤ 0.06, and A is selected from any one or more elements of Mn, Co, Al, Zr, Y, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, Ca, V, Sc, Sr, and B, or is selected from a phosphorus-containing compound containing at least one element of Ti, Al, Mg, Zr, La, and Li. Note that as the phosphorus-containing compound, Li3PO4, lithium titanium aluminum phosphate (LATP), or [LiAl XTi (2ーX) (PO4)3], but are not limited to these.

[0036] In a preferred embodiment of the present invention, when measured by a nitrogen adsorption method, the high nickel positive electrode material has a pore size distribution with a single peak or multiple peaks in a pore size range of 1.5 to 20 nm in a BJH pore size distribution curve, and the high nickel positive electrode material has a total pore volume of 0.0 or less in a pore size range of 1.5 to 20 nm by a single point adsorption method. 1c m 3 / g Within 0.00, preferably 0.00 7c m 3 / g Within.

[0037] In another preferred embodiment of the present invention, the high nickel positive electrode material has a full width at half maximum (FWHM(101)) of a (101) diffraction peak at a diffraction angle 2θ of about 36.6° in a powder X-ray diffraction pattern of the high nickel positive electrode material is 0.080 to 0.180.

[0038] In another preferred embodiment of the invention, the high nickel positive electrode material has a Dv50 particle size of 3-20 μm.

[0039] In another preferred embodiment of the present invention, the specific surface area of ​​the high nickel positive electrode material is 0.33 to 1.5 m 2 / g, and / or the tap density of the high nickel positive electrode material is 1.9 g / cm 3 That's all. And / or the high nickel positive electrode material has a total free lithium content of less than 1800 ppm.

[0040] In another preferred embodiment of the present invention, in said Formula 1, 0.001≦d≦0.04.

[0041] The present invention further provides a method for producing the positive electrode material for a lithium ion battery, comprising mixing the raw materials and then performing at least two firing processes and one coating process.

[0042] However, the raw materials include a Li source, a metal A source, and a nickel-manganese hydroxide precursor.

[0043] In a preferred embodiment of the present invention, the first firing temperature is 700 to 900° C., preferably 790 to 890° C., and more preferably, the constant temperature time is 8 to 40 hours. and / or the second firing temperature is 400 to 800°C, preferably 680 to 800°C, and more preferably the constant temperature time is 5 to 20 hours; More preferably, the firing atmosphere is oxygen.

[0044] In a preferred embodiment of the present invention, in the method for producing the high nickel positive electrode material for lithium ion batteries, the coating treatment is carried out before the final firing.

[0045] In another preferred embodiment of the present invention, in the production method, the Li source is a lithium-containing oxide, a lithium-containing fluoride, or a lithium-containing salt, and preferably, the Li source is one or more selected from anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium acetate, and lithium fluoride.

[0046] In another preferred embodiment of the present invention, the precursor in the raw material has a Dv50 particle size of 2.0 to 20 μm.

[0047] The present invention further provides a high nickel positive electrode material for lithium ion batteries produced by the above-mentioned method.

[0048] The present invention further provides a high nickel cathode material for lithium ion batteries comprising two or more of the above cathode materials.

[0049] The present invention further provides a lithium ion battery cathode comprising a current collector and a cathode material supported on the current collector, said cathode material being a high nickel cathode material for said lithium ion battery.

[0050] The present invention further provides a lithium ion battery comprising a positive electrode, a negative electrode, and a lithium salt-containing electrolyte, the positive electrode being the lithium ion battery positive electrode.

[0051] The lithium ion battery of the present invention further includes a separator and an aluminum laminate film. Specifically, the electrodes include a positive electrode and a negative electrode, the positive electrode is made of a positive electrode current collector, a positive electrode active material coated on the positive electrode current collector, an adhesive, a conductive assistant, and other materials, and the positive electrode active material is a positive electrode material for the lithium ion battery. The negative electrode is made of a current collector, a negative electrode active material coated on the current collector, an adhesive, a conductive assistant, and other materials, the separator is a PP / PE film commonly used in the industry to separate the positive electrode and the negative electrode from each other, and the aluminum laminate film is a covering material for the positive electrode, the negative electrode, the separator, and the electrolyte.

[0052] The adhesive includes polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, poly(vinylidene fluoride), polyethylene, polypropylene, styrene butadiene rubber, acrylic acid (ester)-modified styrene butadiene rubber, epoxy resin, nylon, and the like, and a combination thereof, and its role is to improve the adhesion between positive electrode active material particles and between the positive electrode active material particles and the current collector.

[0053] The conductive assistant includes one or more of a carbon-based material, a metal-based material, and a conductive polymer, the carbon-based material being one or more of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber, the metal-based material being a metal powder or metal fiber of copper, nickel, aluminum, or silver, and the conductive polymer being a polyphenylene derivative.

[0054] The present invention further provides the use of said high nickel positive electrode material for lithium ion batteries, or said lithium ion battery positive electrode, or said lithium ion battery in the field of digital batteries, power batteries or accumulator batteries.

[0055] The beneficial effects of the present invention are further illustrated by the following specific examples.

[0056] The information on the reagents and equipment used in the following examples is as shown in Tables 1-1, 1-2 and 2.

[0057] [Table 1-1]

[0058] [Table 1-2]

[0059] [Table 2]

[0060] Example 1 Mixing of raw materials: Using a 200L plowshare mixer, start and mix to mix 31.78 kg of anhydrous lithium hydroxide, 3.44 kg of cerium oxide, and 100 kg of nickel-manganese hydroxide precursor Ni with a particle size Dv50 of 8.5 μm. 0.9 Mn 0.1 (OH)2 (purchased from Guangdong Integral Energy Co., Ltd.) was added and stirred for 2 hours before preparation for use. First firing: A 36-meter roller hearth kiln was used, the temperature was set to 840°C, oxygen was introduced, and the gas flow rate was 10L / min. The mixed raw materials were placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 35 hours. The raw materials were cooled to room temperature and pulverized by a jet mill to obtain the first fired semi-finished products. Second firing: A 36-meter roller hearth kiln was used, the temperature was set to 700°C, oxygen was introduced, and the gas flow rate was 10L / min. The first firing semi-finished product was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 8 hours. The raw materials were cooled to room temperature and pulverized by a jet mill to obtain the second firing semi-finished product. Coating process: The second calcined semi-finished product was placed in a stirring tank, started to stir, added 150 kg of deionized water, added 1.05 kg of tetrabutyl titanate, mixed for 50 minutes, and filtered to obtain a cake. Third firing: A 36-meter roller hearth kiln was used, the temperature was set to 600°C, oxygen was introduced, and the gas flow rate was 10L / min. The cake after the coating process was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 4 hours. The raw material was cooled to room temperature, crushed by a jet mill, demagnetized and sieved to obtain the positive electrode material.

[0061] After digestion with dilute hydrochloric acid and verification by ICP analysis, the chemical formula of the positive electrode material is Li 1.24 Ni 0.9 Mn 0.1 Ti 0.0051 Ce 0.02 It was O2.

[0062] Example 2 Mixing of raw materials: Using a 200L plowshare mixer, start and mix 48.99 kg of lithium hydroxide monohydrate, 1.2 kg of cobalt oxide, and 100 kg of nickel manganese hydroxide precursor Ni with a particle size Dv50 of 4 μm. 0.8 Mn 0.2 (OH)2 (purchased from Guangdong Integral Energy Co., Ltd.) was added and stirred for 2 hours before preparation for use. First firing: A 36-meter roller hearth kiln was used, the temperature was set to 890°C, oxygen was introduced, and the gas flow rate was 8L / min. The mixed raw materials were placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 28 hours. The raw materials were cooled to room temperature and pulverized by a jet mill to obtain the first fired semi-finished products. Second firing: A 36-meter roller hearth kiln was used, the temperature was set to 750°C, oxygen was introduced, and the gas flow rate was 8L / min. The first firing semi-finished product was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 6 hours. The raw materials were cooled to room temperature and pulverized by a jet mill to obtain the second firing semi-finished product. Coating process: The second calcined semi-finished product was placed in a stirring tank, started to stir, added 120 kg of deionized water, added 1.02 kg of tetrabutyl titanate, mixed for 60 minutes, and filtered to obtain a cake. Third firing: A 36-meter roller hearth kiln was used, the temperature was set at 700°C, oxygen was introduced, and the gas flow rate was 8L / min. The cake after the coating process was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 5 hours. The raw material was cooled to room temperature, crushed by a jet mill, demagnetized and sieved to obtain the positive electrode material.

[0063] After digestion with dilute hydrochloric acid and verification by ICP analysis, the chemical formula of the positive electrode material is Li 1.01 Ni 0.8 Mn 0.2 Co 0.016 Ti 0.0046 It was O2.

[0064] Example 3 Mixing of raw materials: Using a 200L plowshare mixer, start and mix 48.18 kg of lithium hydroxide monohydrate, 2.319 kg of tungsten oxide, 2 kg of cobalt carbonate, 100 kg of D v 50 Nickel manganese hydroxide precursor Ni with a particle size of 15 μm 0.9 Mn 0.1 (OH)2 (purchased from Guangdong Integral Energy Co., Ltd.) was added and stirred for 2 hours before preparation for use. First firing: A 36-meter roller hearth kiln was used, the temperature was set to 830°C, oxygen was introduced, and the gas flow rate was 15L / min. The mixed raw materials were placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 30 hours, and the raw materials were cooled to room temperature and pulverized by a jet mill to obtain the first fired semi-finished products. Coating process: The first calcined semi-finished product was placed in a stirring tank, started to stir, 100 kg of deionized water was added, and 25.4 kg of rubidium carbonate solution (a mixture of rubidium carbonate and water in a ratio of 1:10) was added, mixed for 40 minutes, and filtered to obtain a cake. Second firing: A 36-meter roller hearth kiln was used, the temperature was set at 700°C, oxygen was introduced, and the gas flow rate was 15L / min. The cake after the coating process was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 9 hours. The raw material was cooled to room temperature, crushed by a jet mill, demagnetized and sieved to obtain the positive electrode material.

[0065] After digestion with dilute hydrochloric acid and verification by ICP analysis, the chemical formula of the positive electrode material is Li 1.06 Ni 0.9 Mn 0.1 Co 0.02 W 0.01 Rb 0.02 It was O2.

[0066] Example 4 Mixing of raw materials: Using a 200L plowshare mixer, start and mix 46.06 kg of lithium hydroxide monohydrate, 100 kg of nickel manganese hydroxide precursor Ni with a particle size Dv50 of 2.0 μm. 0.85 Mn 0.15 (OH)2 (purchased from Guizhou Zhongwei Zhengyuan New Material Co., Ltd.) was added and stirred for 2 h before being prepared for use. First firing: A 36-meter roller hearth kiln was used, the firing temperature was set to 840°C, oxygen was introduced (oxygen flow rate 12 L / min), and the mixed raw materials were fed into the equipment for the first firing. The temperature was kept constant for 16 hours, and the raw materials were cooled to room temperature and pulverized in a jet mill to obtain the first fired semi-finished product. Second firing: A 36-meter roller hearth kiln was used, the firing temperature was set to 800°C, oxygen (oxygen flow rate 8L / min) was flowed in, and the first fired semi-finished product was put into the 36-meter roller hearth kiln for the second firing, and the temperature was kept constant for 18 hours. The raw material was cooled to room temperature, crushed in a jet mill, and then demagnetized to obtain the second fired semi-finished product. Coating process: The second fired semi-finished product was placed in a stirring tank, started to stir, 100 kg of deionized water was added, stirred for 10 minutes, suction filtered, baked, and the baked semi-finished product was placed in a mixer, started to stir, added 1.77 kg of ammonium heptamolybdate, and mixed for 30 minutes. Third firing: A 36-meter roller hearth kiln was used, the firing temperature was set to 600°C, oxygen was introduced (oxygen flow rate: 5 L / min), and the coated raw materials were fed into the 36-meter roller hearth kiln for the third firing, which was held at a constant temperature for 10 hours. The raw materials were then cooled to room temperature, crushed in a jet mill, demagnetized, and sieved to obtain the positive electrode material.

[0067] After digestion with dilute hydrochloric acid and verification by ICP analysis, the chemical formula of the positive electrode material is Li 1.04 Ni 0.85 Mn 0.15 Mo 0.01 It was O2.

[0068] Example 5 Mixing of raw materials: Using a 200L plowshare mixer, start and mix 46.94 kg of lithium hydroxide monohydrate, 100 kg of nickel manganese hydroxide precursor Ni with a particle size Dv50 of 14.0 μm. 0.85 Mn 0.15 (OH)2 (purchased from Guizhou Zhongwei Zhengyuan New Material Co., Ltd.) was added and stirred for 2 h before being prepared for use. First firing: A 36-meter roller hearth kiln was used, the firing temperature was set to 810°C, oxygen was introduced (oxygen flow rate 12 L / min), the mixed raw materials were fed into the equipment and the first firing was carried out, the temperature was kept constant for 12 hours, the raw materials were cooled to room temperature and crushed in a jet mill to obtain the first fired semi-finished product. Coating process: The first fired semi-finished product was placed in a stirring tank, started to stir, 100 kg of deionized water was added, stirred for 20 minutes, suction filtered, baked, and the baked semi-finished product was placed in a mixer, started to stir, 0.4 kg of boron oxide was added, and mixed for 30 minutes. Second firing: A 36-meter roller hearth kiln was used, the firing temperature was set to 400°C, oxygen was introduced (oxygen flow rate 5L / min), and the coated raw materials were placed in the 36-meter roller hearth kiln for the third firing, which was held at a constant temperature for 5 hours. The raw materials were then cooled to room temperature, demagnetized, and sieved to obtain the positive electrode material.

[0069] After digestion with dilute hydrochloric acid and verification by ICP analysis, the chemical formula of the positive electrode material is Li 1.06 Ni 0.85 Mn 0.15 B 0.005 It was O2.

[0070] Example 6 Mixing of raw materials: Using a 200L plowshare mixer, start and mix 29.07 kg of anhydrous lithium hydroxide, 2.95 kg of strontium carbonate, 100 kg of nickel-manganese hydroxide precursor Ni with a Dv50 particle size of 8.0 μm. 0.95 Mn 0.05 (OH)2 (purchased from Guangdong Integral Energy Co., Ltd.) was added and stirred for 2 hours before preparation for use. First firing: A 36-meter roller hearth kiln was used, the temperature was set to 790°C, oxygen was introduced, and the gas flow rate was 10L / min. The mixed raw materials were placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 40 hours. The raw materials were cooled to room temperature and pulverized by a jet mill to obtain the first fired semi-finished products. Coating process: The first calcined semi-finished product was placed in a stirring tank, started to stir, 100 kg of deionized water was added, and 28.5 kg of magnesium acetate solution (a mixture of magnesium acetate and water in a ratio of 1:10) was added, mixed for 60 minutes, and filtered to obtain a cake. Second firing: A 36-meter roller hearth kiln was used, the temperature was set to 680°C, oxygen was introduced, and the gas flow rate was 10L / min. The cake after the coating process was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 5 hours. The raw material was cooled to room temperature, crushed by a jet mill, demagnetized and sieved to obtain the positive electrode material.

[0071] After digestion with dilute hydrochloric acid and verification by ICP analysis, the chemical formula of the positive electrode material is Li 1.14 Ni 0.95 Mn 0.05 Sr 0.02 Mg 0.02 It was O2.

[0072] Example 7 Mixing of raw materials: Using a 200L plowshare mixer, start and mix 48.18 kg of lithium hydroxide monohydrate, 1.9 kg of strontium carbonate, 100 kg of nickel manganese hydroxide precursor Ni with a Dv50 particle size of 3.5 μm. 0.9 Mn 0.1 (OH)2 (purchased from Guangdong Integral Energy Co., Ltd.) was added and stirred for 2 hours before preparation for use. First firing: A 36-meter roller hearth kiln was used, the temperature was set to 860°C, oxygen was introduced, and the gas flow rate was 15L / min. The mixed raw materials were placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 35 hours. The raw materials were cooled to room temperature and pulverized by a jet mill to obtain the first fired semi-finished products. Second firing: A 36-meter roller hearth kiln was used, the temperature was set to 750°C, oxygen was introduced, and the gas flow rate was 15L / min. The first firing semi-finished product was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 7 hours. The raw materials were cooled to room temperature and pulverized by a jet mill to obtain the second firing semi-finished product. Coating process: The second calcined semi-finished product was placed in a stirring tank, started to stir, 100 kg of deionized water was added, and 8.4 kg of aluminum nitrate nonahydrate solution (aluminum nitrate nonahydrate and water mixed in a ratio of 1:5) was added, mixed for 40 minutes, and filtered to obtain a cake. Third firing: A 36-meter roller hearth kiln was used, the temperature was set at 700°C, oxygen was introduced, and the gas flow rate was 15L / min. The cake after the coating process was placed in a sagger and sent to the roller hearth kiln for firing. The constant temperature time was 9 hours. The raw material was cooled to room temperature, crushed by a jet mill, demagnetized and sieved to obtain the positive electrode material.

[0073] After digestion with dilute hydrochloric acid and verification by ICP analysis, the chemical formula of the positive electrode material is Li 1.1 Ni 0.9 Mn 0.1 Sr 0.015 Al 0.003 It was O2.

[0074] Example 8 The positive electrode materials of Examples 3 and 7 were mixed in a mass ratio of 1:1 to obtain a mixed positive electrode material.

[0075] Example 9 The positive electrode materials of Examples 3 and 7 were mixed in a mass ratio of 7:3 to obtain a mixed positive electrode material.

[0076] (Test Example 1) The characteristic parameters of the high nickel positive electrode materials produced in Examples 1 to 9 were measured by the following methods.

[0077] (1) Method for measuring pore size distribution curve Using an automatic specific surface area and pore distribution measuring device (TriStarII3020), 4 g of the positive electrode powder material was placed in a sample tube for measurement, and degassing treatment was performed at 200 ° C for 1 hour to thoroughly remove moisture from the measurement sample. Next, using a nitrogen adsorption method using liquid nitrogen, the adsorption side and desorption side isotherms were measured in the relative pressure P / P0 (P0 ≒ 665 mmHg) range of 0.01 to 0.995. Using the desorption side isotherm, a pore size distribution curve was obtained with the pore size on the horizontal axis and the pore volume on the vertical axis, and the pore size distribution curve of the high nickel positive electrode material produced in Example 7 is as shown in Figure 1. As can be seen from Figure 1, the pore size distribution curve has one single peak within the pore size range of 1.5 to 20 nm. Table 3 shows the measurement results of the pore size ranges of the high-nickel positive electrode materials produced in Examples 1 to 9 and the total pore volumes in the pore sizes of 1.5 to 20 nm measured by the single-point adsorption method.

[0078] (2) Measurement method for specific surface area In the present invention, the specific surface area was measured by an automatic specific surface area / pore distribution measuring device (TriStar II 3020) with reference to the gravimetric method of the gas adsorption BET method in GB / T 19587-2004. The measurement results are shown in Table 3.

[0079] (3) Particle size measurement method In the present invention, the particle size was measured by a Malvern Master Size 2000 laser particle size distribution analyzer according to GB / T19077-2016 particle size distribution analysis laser diffraction method, 1g of powder was weighed out and added to 60mL of pure water, and ultrasonicated for 5 minutes, and the sample was injected into a sample injector for measurement, and the measurement data was recorded. The measurement results are shown in Table 3.

[0080] A Master Size 2000 laser particle size analyzer was used, the detection angle was 0-135°, the test principle was Mie theory, the ultrasonic intensity was 40kHz 180W, the particle refractive index was 1.692, the particle absorptivity was 1, the sample measurement time was 6 seconds, the number of background measurement snaps was 6000, and the light blocking degree was 8-12%.

[0081] (4)XRD measurement method An X'Pert PRO MPD diffractometer was used, with a Cu tube, a wavelength of 1.54060, and a Be window. In the incident light path, the Soller slit was 0.04 rad, the divergence slit was 1 / 2°, the light shield was 10 mm, and the anti-scattering slit was 1°. In the diffraction light path, the anti-scattering slit was 8.0 mm, the Soller slit was 0.04 rad, and a large Ni filter. The scanning range was 10 to 80°, the scanning step width was 0.013°, the measurement time per step was 30.6 seconds, the voltage was 40 kV, the current was 40 mA, and the analysis software was High-Score Plus. The X-ray diffraction pattern of the high nickel positive electrode material produced in Example 6 is as shown in FIG. 2, and the measurement results of the half-width FWHM (101) corresponding to the (101) diffraction peak at a diffraction angle 2θ of around 36.6° of the high nickel positive electrode material produced in Examples 1 to 9 are as shown in Table 3.

[0082] (5) Method for measuring tap density Using a 100mL measuring cylinder, weigh out m(50±0.5)g of powdered material, pour the raw material into the measuring cylinder so that it covers the bottom of the cylinder, read the scale on the upper edge of the raw material, record it as V1, place the measuring cylinder containing the powdered material in the BT-303 tap density tester, set the parameters to 3±0.1mm amplitude and 3000 vibrations, start the machine, and when the vibration is finished, remove the measuring cylinder and read the scale V2 on the upper edge of the powdered material. The tap density was (V1-V2) / m. The measurement results are shown in Table 3.

[0083] (6) Measurement method for total free lithium Accurately weigh out 30g±0.01g of sample, add the sample to a 250mL Erlenmeyer flask, add a magnetic stirrer, and add 100mL deionized water. Place the Erlenmeyer flask on the magnetic stirrer, start the device, and stir for 30 minutes. Filter the mixed solution with qualitative filter paper and a funnel. Take 50mL of the filtrate with a 50mL pipette and add it to a 100mL beaker and add a stirrer. Place the beaker on the magnetic stirrer and add 2 drops of phenolphthalein indicator. Titrate with 0.05mol / L hydrochloric acid standard solution until the color of the solution changes from red to colorless, and record the volume V1 (endpoint 1) of the 0.05mol / L hydrochloric acid standard solution. Add 2 drops of methyl red indicator, and the color of the indicator changes from colorless to yellow. Titrate with 0.05mol / L hydrochloric acid standard solution until the color of the solution changes from yellow to orange. The beaker was placed in a heating furnace and heated until the solution boiled (the color of the solution changed from orange to yellow). The beaker was removed and cooled to room temperature. The beaker was then placed on a magnetic stirrer and titrated with 0.05 mol / L hydrochloric acid standard solution until the color of the solution changed from yellow to pale red, and the volume V2 (end point 2) of the 0.05 mol / L hydrochloric acid standard solution was recorded. The total amount of free lithium was calculated using the following formula, and the measurement results are shown in Table 3.

[0084] Total free lithium amount = V2 x 0.05 x 6.94 x 2 x 100% / (m x 1000), The total free lithium amount is expressed as 100%. m is the mass of the sample in g; V2 is the second titration endpoint, in mL; 6.94 is the atomic weight of lithium.

[0085] [Table 3]

[0086] (Test Example 2) Lithium-ion battery fabrication and characterization: Pouch cell 454261 was manufactured in the following manner. Preparation of positive electrode: Each of the high nickel positive electrode materials prepared in Examples 1 to 9 of the present invention, conductive carbon black (SP), and adhesive polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 (the weight ratio of the positive electrode material to NMP was 2.1:1), thoroughly mixed and stirred to form a uniform slurry, which was then coated on an aluminum foil current collector, dried, and pressed to obtain a plate.

[0087] Negative electrode preparation: The artificial graphite for the negative electrode, conductive carbon black (SP), carboxymethyl cellulose (CMC), and adhesive (SBR) were mixed in a weight ratio of 95:1:1:3 with a sufficient amount of pure water, stirred to form a uniform slurry, coated onto a copper foil current collector, dried, and pressed to obtain a plate.

[0088] The separator was a PP / PE composite film material. After pressing, the positive and negative plates were spot-welded with tabs, and the separator was inserted. The plate was then wound up in a winder and placed in a pouching jig, the top and sides were sealed, and the plate was then placed in an oven for heating and drying. After that, 9g of electrolyte was injected in an environment with a relative humidity of less than 1.5%, and a mixed solvent with a mass ratio of EC:DEC:DMC=1:1:1 was used as the electrolyte, and the electrolyte was 1M lithium hexafluorophosphate. After the electrolyte was injected and formed for 48 hours, it was vacuumed and sealed. The cell model number was 454261.

[0089] The battery characteristics were tested using a battery tester (provided by Zhejiang Hangzhou Ke Technology) using the following method.

[0090] 1) Capacity test The manufactured pouch cell was connected to a test rack, and a test program was started. The steps were set as follows: set the test temperature to 25°C, leave it for 4 hours, charge it at a constant current and constant voltage for 4 hours (e.g., charge it to 4.2V at 1 / 3C), stop it once, leave it, and discharge it at a constant current (e.g., discharge it to a voltage of 3.0V at 1 / 3C), obtain the capacity under the current and voltage, and repeat the steps to obtain capacity data under different current and voltage conditions.

[0091] 2) Cycle test The battery that had passed the capacity test was connected to a test rack, and a test program was started, with the following steps: set the test temperature at 45° C., leave it for 4 hours, charge at a constant current for 4 hours (e.g., charge to 4.2 V at 1 C, or charge to 4.3 V at 1 C), switch to a constant voltage and charge (e.g., charge to 4.2 V in 2 hours, or charge to 4.3 V in 2 hours), leave it for 5 minutes, discharge at a constant current for 4 hours (e.g., to a voltage of 3.0 V at 1 C), leave it for 5 minutes, and repeat the steps starting with the constant current charge to perform a cycle test, thereby obtaining the capacity retention rate at different voltages and different cycle numbers.

[0092] 3) Post-cycle DC internal resistance (DCR) increase test In the cycle test step 2), a step of constant current 30 seconds discharge was added before the constant current discharge (the voltage difference within 30 seconds was recorded and divided by the current to obtain the DCR), but the rest was the same. By repeating the steps starting from the constant current charge and performing the cycle test, the DCR increase rate at different cycle numbers (the difference between the DCR after the cycle and the DCR after the first cycle was divided by the DCR after the first cycle) could be obtained, and the test results are shown in Table 4.

[0093] 4) Rate characteristics The manufactured pouch cell was connected to the test rack, and the test program was started. The steps were set as follows. The test temperature was set to 25°C, and the battery was left to stand for 4 hours, and then charged to 4.2V at a constant current and constant voltage of 1 / 3C. When the current reached 0.02C, the battery was stopped, left to stand, and discharged to a voltage of 3.0V at 1 / 3C, and the 1 / 3C discharge capacity of the battery was recorded. The battery was left to stand for 4 hours, and then charged to 4.2V at a constant current and constant voltage of 1C. When the current reached 0.02C, the battery was stopped, left to stand, and discharged to a voltage of 3.0V at 1C, and the 1C discharge capacity of the battery was recorded. The battery was left to stand for 4 hours, and then charged to 4.2V at a constant current and constant voltage of 2C. When the current reached 0.02C, the battery was stopped, left to stand, and discharged to a voltage of 3.0V at 2C, and the 2C discharge capacity of the battery was recorded.

[0094] [Table 4]

[0095] As can be seen from Table 3, the high nickel positive electrode materials for lithium ion batteries prepared in Examples 1 to 9 of the present invention have a total pore volume of 0.004 in the pore diameter range of 1.5 to 20 nm measured by nitrogen adsorption method. 3c m 3 / g Therefore, the positive electrode material has a porous structure with a pore size range of 1.7 to 19 nm. The tap density of the high nickel positive electrode material produced by the present invention is 1.9 g / cm 3 The specific surface area is 0.33 to 0.95 m 2 / g, and the Dv50 particle size was 3.3 to 17.3 μm. The XRD diffraction pattern shows that the full width at half maximum (FWHM(101)) of the (101) diffraction peak at a diffraction angle 2θ of about 36.6° in the powder X-ray diffraction pattern of the positive electrode material is 0.093 to 0.133.

[0096] As can be seen from Table 4, the lithium ion battery produced in the high nickel positive electrode material for lithium ion batteries produced in Examples 1 to 9 of the present invention has a capacity of 181 to 200.7 mAh / g at 1 / 3 C current and 4.2 V voltage, a discharge capacity of 175.3 to 194.6 mAh / g at 2 C current, a capacity retention rate of 87 to 94% after 200 cycles at 4.2 V, and a DCR increase rate of 19 to 30% after 200 cycles at 4.2 V. The high nickel positive electrode material produced in the present invention has a small pore diameter, provides many paths for the movement of lithium ions, and the path is short, so that it has a high capacity and good rate characteristics. The half-width FWHM (101) of the (101) diffraction peak at a diffraction angle 2θ of about 36.6 ° in the powder X-ray diffraction pattern of the positive electrode material is 0.093 to 0.133, so the material has good structural stability, a good capacity retention rate, and a small increase in DC internal resistance. In Examples 8 and 9 of the present invention, by mixing positive electrode materials with different particle sizes, the tap density of the high-nickel positive electrode material for lithium-ion batteries is further increased, a good balance is achieved between capacity and cycle characteristics, and the increase in DC internal resistance is also reduced.

[0097] In summary, compared with the conventional lithium ion battery positive electrode material, the present invention obtains a cobalt-free modified high nickel lithium ion battery positive electrode material by adding a modifying element and performing at least two sintering processes and one coating process, which has a unique porous structure and crystal structure, and the porous structure of the positive electrode material provides more paths for the movement of lithium ions and the paths are shorter, so that the lithium ion battery not only has higher capacity and good rate characteristics, but also has good structural stability due to the crystal structure, so that the capacity loss during the charge and discharge of the lithium ion battery is small, the cycle characteristics are excellent, and the increase in DC internal resistance is small, and the capacity, rate characteristics and cycle characteristics of the cobalt-free positive electrode material are effectively balanced.

[0098] The above are merely preferred embodiments of the present invention, and are not intended to limit the present invention in any way. Any modifications, equivalent replacements, or improvements made without departing from the spirit and principles of the present invention shall be included in the scope of protection of the present invention.

[0099] (Supplementary Note) (Supplementary Note 1) It has a porous structure, and its chemical formula 1 is Li 1+a Ni b Mn c A d The elemental composition shown in O2, provided that 0.01 ≦ a ≦ 0.24, 0.79 < b ≦ 0.96, 0.01 < c ≦ 0.20, 0 < d ≦ 0.06, and A is selected from any one or more elements of Mn, Co, Al, Zr, Y, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, Ca, V, Sc, Sr, and B, or selected from a phosphorus-containing compound containing at least one element of Ti, Al, Mg, Zr, La, and Li A high-nickel cathode material for a lithium-ion battery, characterized in that

[0100] (Supplementary Note 2) When measured by the nitrogen adsorption method, it has a single-peak or multi-peak pore size distribution within the pore size range of 1.5 to 20 nm in the BJH pore size distribution curve, and the high-nickel cathode material has a one-point adsorption total pore volume of 0.0 1c m 3 / g or less The high-nickel cathode material for a lithium-ion battery according to Supplementary Note 1, characterized in that

[0101] (Supplementary Note 3) The high-nickel cathode material has a one-point adsorption total pore volume of 0.00 7c m 3 / g or less The high-nickel cathode material for a lithium-ion battery according to Supplementary Note 2, characterized in that

[0102] (Supplementary Note 4) The full width at half maximum FWHM(101) of the (101) diffraction peak at a diffraction angle 2θ of around 36.6° in the powder X-ray diffraction pattern of the cathode material is 0.080 to 0.180 2. The high nickel positive electrode material for lithium ion batteries according to claim 1,

[0103] (Appendix 5) The positive electrode material has a Dv50 particle size of 3 to 20 μm. 2. The high nickel positive electrode material for lithium ion batteries according to claim 1,

[0104] (Appendix 6) The specific surface area of ​​the positive electrode material is 0.33 to 1.5 m 2 / g, 2. The high nickel positive electrode material for lithium ion batteries according to claim 1,

[0105] (Appendix 7) The tap density of the positive electrode material is 1.9 g / cm 3 That's all. 2. The high nickel positive electrode material for lithium ion batteries according to claim 1,

[0106] (Appendix 8) The total free lithium content of the positive electrode material is less than 1800 ppm; 2. The high nickel positive electrode material for lithium ion batteries according to claim 1,

[0107] (Appendix 9) In the above formula 1, 0.001≦d≦0.04; 2. The high nickel positive electrode material for lithium ion batteries according to claim 1,

[0108] (Appendix 10) The raw materials are mixed and then subjected to at least two firing processes and one coating process. 2. A method for producing a high-nickel positive electrode material for lithium-ion batteries according to claim 1.

[0109] (Appendix 11) The first firing temperature is 700 to 900°C. The second firing temperature is 400 to 800°C. The method of claim 10,

[0110] (Appendix 12) The first firing temperature is 790 to 890°C. The second firing temperature is 680-800°C. The method of claim 10,

[0111] (Appendix 13) The constant temperature time for the first firing is 8 to 40 hours. The constant temperature time for the second firing is 5 to 20 hours. The method of claim 10,

[0112] (Appendix 14) The firing atmosphere is oxygen. The method of claim 10,

[0113] (Appendix 15) The coating process is carried out before the final firing. The method of claim 10,

[0114] (Appendix 16) The Li source is a lithium-containing oxide, a lithium-containing fluoride, or a lithium-containing salt; The method of claim 10,

[0115] (Appendix 17) The Li source is one or more selected from anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium acetate, and lithium fluoride; The method of claim 16,

[0116] (Appendix 18) Produced by the production method according to any one of appendices 10 to 17; A high nickel positive electrode material for lithium ion batteries.

[0117] (Appendix 19) The positive electrode material according to any one of claims 1 to 9 or any one of claims 10 to 17 is produced by the method, A high nickel positive electrode material for lithium ion batteries.

[0118] (Appendix 20) A high-nickel positive electrode material for a lithium ion battery comprising a current collector and a positive electrode material supported on the current collector, the positive electrode material being produced by the production method described in any one of appendices 1 to 9 or any one of appendices 10 to 17; A lithium ion battery positive electrode comprising:

[0119] (Appendix 21) A positive electrode, a negative electrode, and a lithium salt-containing electrolyte, wherein the positive electrode is the lithium ion battery positive electrode described in Appendix 20. A lithium-ion battery characterized by:

Claims

1. It has a porous structure, and the chemical formula 1 is Li 1+a Ni b Mn c A d O 2 wherein, 0.01≦a≦0.24, 0.79<b≦0.96, 0.01<c≦0.20, and 0<d≦0.06, and A is one or more elements selected from Mn, Co, Al, Zr, Y, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, Ca, V, Sc, Sr, and B; When measured by nitrogen adsorption, the BJH pore size distribution curve has a single peak or multiple peaks in the pore size range of 1.5 to 20 nm, and the high nickel positive electrode material has a single-point adsorption total pore volume of 0.01 cm in the pore size range of 1.5 to 20 nm. 3 / g or less, The full width at half maximum (FWHM) (101) of the (101) diffraction peak at a diffraction angle 2θ of about 36.6° in the powder X-ray diffraction pattern of the positive electrode material is 0.080 to 0.

180. A high nickel positive electrode material for lithium ion batteries.

2. The high nickel positive electrode material has a pore diameter in the range of 1.5 to 20 nm and a total pore volume of 0.007 cm3 as measured by single point adsorption. 3 / g or less, 2. The high nickel positive electrode material for lithium ion batteries according to claim 1.

3. The positive electrode material has a Dv50 particle size of 3 to 20 μm; 2. The high nickel positive electrode material for lithium ion batteries according to claim 1.

4. The specific surface area of ​​the positive electrode material is 0.33 to 1.5 m 2 / g, 2. The high nickel positive electrode material for lithium ion batteries according to claim 1.

5. The tap density of the positive electrode material is 1.9 g / cm 3 That's all.

2. The high nickel positive electrode material for lithium ion batteries according to claim 1.

6. The total free lithium content of the positive electrode material is less than 1800 ppm; 2. The high nickel positive electrode material for lithium ion batteries according to claim 1.

7. In the formula 1, 0.001≦d≦0.04; 2. The high nickel positive electrode material for lithium ion batteries according to claim 1.

8. The raw materials are mixed, followed by at least two firing steps and one coating step. The method for producing the high nickel positive electrode material for lithium ion batteries according to any one of claims 1 to 7.

9. The first firing temperature is 700 to 900°C. The second firing temperature is 400 to 800°C. The method according to claim 8 .

10. The first firing temperature is 790 to 890°C. The second firing temperature is 680 to 800°C. The method according to claim 8 .

11. The constant temperature time for the first firing is 8 to 40 hours. The constant temperature time for the second firing is 5 to 20 hours. The method according to claim 8 .

12. The firing atmosphere is oxygen. The method according to claim 8 .

13. The coating process is carried out before the final firing. The method according to claim 8 .

14. The raw material includes a Li source, and the Li source is a lithium-containing oxide, a lithium-containing fluoride, or a lithium-containing salt. The method according to claim 8 .

15. The Li source is one or more selected from anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium acetate, and lithium fluoride; The method according to claim 14 .

16. The cathode material according to any one of claims 1 to 7, A high nickel positive electrode material for lithium ion batteries.

17. A current collector and a positive electrode material supported on the current collector, the positive electrode material being the high nickel positive electrode material for lithium ion batteries according to any one of claims 1 to 7. A lithium ion battery positive electrode comprising:

18. A lithium ion battery comprising a positive electrode, a negative electrode, and a lithium salt-containing electrolyte, the positive electrode being the lithium ion battery positive electrode according to claim 17. A lithium-ion battery characterized by:

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, positive electrode and secondary battery

    JP2015118945A

  • Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery

    JP2018106892A

  • Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery and lithium secondary battery

    JP2018206750A

  • Positive electrode active material for lithium ion secondary batteries, method for producing same, and lithium ion secondary battery

    WO2021045025A1